Localised learning based portfolio management for stock trading using intelligent fuzzy neural approach - Mok, Luen Sheng. (2009)
This project discussed the possibility of using artificial intelligence (AI) techniques to formulate trading decisions. It will be used to predict a stock’s closing price. It serves as an additional analyzing tool for analysts in their research and observing the trends of stocks’ movements.